Spectrum of ABO and Rh blood group in Nepali medical students - Joshi, Bishal; Kar, Sanjit Kumar; Shrestha, Laxmi; Yadav, Shankar (Journal of Chitwan Medical College, 2020)
Background: ABO and Rh systems are most important types of blood group systems that should be taken into consideration during blood transfusion. Many studies have been done across the globe to determine the distribution of these blood groups among different strata of population. But there are very few studies done in Nepali population. Therefore, in this study we aimed to find out the distribution of blood groups among Nepali medical students and to compare it with the other studies done in Nepal and other countries of the World. Methods: This was a retrospective study, containing the data of ABO and Rh blood groups of medical students recorded over a period of 21 years in Department of Physiology of Universal College of Medical Sciences, Bhairahawa, Nepal. The blood group was determined by open slide test method by using commercially available standard monoclonal antibody. Results: A total of 2031 Nepali medical students were included in the study. Among them 1147 were male and 884 were female. In the present study we found that the most common blood group was O (739, 36.4%) followed by B (624, 30.7%) and A (522, 25.7%) and least common blood group was AB (146, 7.2%). Among all participants 96.8% of the people were Rh positive and 3.2% were Rh negative. Conclusions: This study done in Nepali medical students can provide a new insight for the further study of distribution of blood groups in Nepali population. A study with high sample size, representing every zones of Nepal is the demand of future.